Check in the mail or more in the paycheck: does the effectiveness of fiscal stimulus depend on how it is delivered? - Claudia R. Sahm; Matthew D. Shapiro; Joel Slemrod (European Central Bank (ECB), 2011)
Recent fiscal policies have aimed to stimulate household spending. In 2008, most households received one-time economic stimulus payments. In 2009, most working households received the Making Work Pay tax credit in the form of reduced withholding; other households, mainly retirees, received one-time payments. This paper quantifies the spending response to these different policies and examines whether the spending response differed according to whether the stimulus was delivered as a one-time payment or as a flow of payments in the form of reduced withholding. Based on responses from a representative sample of households in the Thomson Reuters/University of Michigan Surveys of Consumers, the paper finds that the reduction in withholding led to a substantially lower rate of spending than the one-time payments. Specifically, 25 percent of households reported that the one-time economic stimulus payment in 2008 led them to mostly increase their spending while only 13 percent reported that the extra pay from the lower withholding in 2009 led them to mostly increase their spending. The paper uses several approaches to isolate the effect of the delivery mechanism from the changing aggregate and individual conditions. Responses to a hypothetical stimulus in 2009, examination of “free responses” concerning differing responses to the policies, and regression analysis controlling for individual economic conditions and demographics all support the primary importance of the income delivery mechanism in determining the spending response to the policies.
Keywords: H31; E62; C83; 330; Fiscal Stimulus; Marginal Propensity to Consume; survey responses; tax rebates